2002
DOI: 10.1592/phco.22.3.256.33543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Complementary and Alternative Medicine in the Largest United States‐Mexico Border City

Abstract: A wide range of CAM use was documented in this study. Our results indicate that Hispanics in this area use CAM at a higher rate than national trends. Many of these therapies can adversely affect a variety of disease states and drug therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 15 publications
1
55
3
Order By: Relevance
“…Patients with language and literacy issues are a population with significant CAM use. As such, this patient population was targeted for study during the 2nd International 27 However, in our study, a lack of personnel and time, and the possibility of creating methodologic inconsistencies prohibited administration of the survey by clinic practitioners, including certified interpreters. Providing the survey only in English may have prohibited the non-English-speaking population served by the clinic from study participation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Patients with language and literacy issues are a population with significant CAM use. As such, this patient population was targeted for study during the 2nd International 27 However, in our study, a lack of personnel and time, and the possibility of creating methodologic inconsistencies prohibited administration of the survey by clinic practitioners, including certified interpreters. Providing the survey only in English may have prohibited the non-English-speaking population served by the clinic from study participation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…3 This trend is seen more recently in 2002, when the prevalence was 74.6% if prayer was included and 49.8% if prayer was excluded. 4 Different studies evaluating CAM use and ethnicity have produced very different results, from a prevalence of use (not including prayer) of 77% among Hispanics in a Mexican border town 5 to one of 27% among Hispanics participating in a national survey. 6 The most common reasons for using CAM among US adults of varied ethnicities are pain (35%) and colds (9.5%).…”
mentioning
confidence: 99%
“…1,3,5 Cognitive interviews with 5 Spanish-speaking community members were conducted to evaluate fl ow and understanding of the survey questions and to modify the questions accordingly.…”
mentioning
confidence: 99%
“…Today Aloe is still a popular folk medicine among peoples of Indian, Chinese, and Mexican origin. Recent surveys have indicated that it is one of the three most used botanicals of middle-aged Mexican women (Zenk et al, 2001); elderly Hispanic and non-Hispanic patients (Zeilmann et al, 2003); asthmatic patients in Trinidad (Clement et al, 2005); low-income, nutritionally vulnerable children in Kansas and Wisconsin (Lohse et al, 2006), Italian women (Zaffani et al, 2006); and households in Texas (Rivera et al, 2002) and Europe (Pahor, 1995).…”
Section: Uses Medicinalmentioning
confidence: 99%